LITERATURE REVIEW: PERAN CARING LEADERSHIP TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP - Ni Kadek Novi Mirayani; Ni Made Nopita Wati; Made Nursari (Jurnal Keperawatan Priority, 2021)
Most human resources in terms of the amount of time together with clients or patients in the hospital are nurses. The era of globalization as now does not need to be found from patients or families Achievement or work performance derived from the word work performance (work performance or achievements that have been achieved by someone). Work processes that produce the cooperation needed to produce the best results. The behavior of leaders who care about their staff or employees is called leadership concern. Caring for leadership as a leadership style can facilitate the needs of nurses so that it will improve nurse performance. The purpose of this literature review is to analyze the results of research on the role of caring leadership in the performance of nurses in the inpatient room. The method used is a literature review by searching articles both internationally and nationally, from the Google Scholar database, E-Journal, and SINTA through advanced searches with keywords caring leadership, nurse performance, inpatient care. The results of several articles obtained, only 6 articles that fit the criteria. The review results show that there is a significant relationship between caring leadership and nurse performance. The application of caring leadership can be done through giving attention to nurses, taking nurses' decisions to make decisions, and giving respect to nurses who work caring for patients. Caring leadership is proven to make nurses work more optimally, win turnover, and produce nurses who are more responsible.